ANALISIS PENGARUH KUALITAS INFORMASI, KUALITAS SISTEM DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada Pelanggan Traveloka di Kota Semarang) - Rinaldi, Adhitya; Santoso, Suryono Budi (Diponegoro Journal of Management, 2018)
Online Travel Agent (OTA) is a new business that arises due to technological developments.  The  promising  potential  of  OTA  in  Indonesia  makes  many  new  OTA emerged and increased in competition. Based on research conducted by W&S Digital Market  Research  (2014),  Traveloka  is  in  the  "switching  out"  zone  where  6.7%  of Traveloka customers choose to switch to another OTA. This indicates that there is a decrease in repurchase intention in customers of Traveloka. Therefore, it needs to conduct some  research  to  increase  the  repurchase  intention.  Based  on  the  background,  the research was conducted to analyze the influence of information quality, system quality and service  quality  to  repurchase  intention  with  customer’s  satisfaction  as  intervening variable.The sampling method that being used was a non-probability purposive sampling by distributing questionnaires to the respondents who are specifically addressed to the people of Semarang City. In this study, it developed a theoretical model by proposing four hypotheses to be tested using the Structural Equation Modeling (SEM) analysis tool operated through the AMOS 22.0 program. The size of the sample in this research was between 100 - 200 samples. This study obtained 126 valid respondents.The result of the research shows that the repurchase intention can be improved by improving information quality, system quality and service quality. Those are the qualities that influence customer's satisfaction as the determinant of success to increase repurchase intention. The most influential factor in determining the repurchase intention, with satisfaction as a variable intervening, is system quality